IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP NEGERI 20 KOTA KUPANG PADA MATERI SISTEM PERNAPASAN - Verensiana S. Lein; Yusnaeni Yusnaeni; Adevalentin K. M. Lesik (SINERGI : Jurnal Riset Ilmiah, 2026)
This Classroom Action Research aims to enhance the engagement and learning outcomes of Grade VIII students at SMP Negeri 20 Kupang City through the implementation of the Problem-Based Learning (PBL) model in the study of the respiratory system. The research subjects consisted of 29 students: 16 males and 13 females. The study was conducted over two cycles, each comprising the stages of planning, action implementation, observation, and reflection. Data were collected using observation, testing, and documentation techniques. Research instruments included observation sheets for teacher and student activities, as well as test instruments consisting of pre-test and post-test questions. The data were analyzed descriptively to determine the improvements in teacher activity, student activity, and student learning outcomes. The results indicate that: (1) teacher activity increased by 5.68% based on observations; (2) student activity increased by 15.64% based on observations; and (3) student learning outcomes improved by 31.04%. These findings demonstrate that implementing the Problem-Based Learning (PBL) model can enhance teacher activity, student activity, and student learning outcomes regarding the respiratory system among Grade VIII students at SMP Negeri 20 Kupang City.